Sistema de cruzamento em populações de Handroanthus heptaphyllus (Vell.) Mattos e suas implicações para a coleta de sementes para fins de conservação e melhoramento genético - Mori, Neide Tomita [UNESP]; Mori, Edson Seizo [UNESP]; Tambarussi, Evandro Vagner; De Moraes, Mario Luiz Teixeira [UNESP]; Sebbenn, Alexandre Magno (My University, 2015)
Handroanthus heptaphyllus is a long-lived tropical tree, insect-pollinated, common in secondary vegetation, and is economical useful for urban and forest restoration purposes. However, when considering seed harvest for reforestation, it is fundamental to know the mating system of populations, since that determines the effective size of the sample. Therefore, the objective of this work was to study the mating system of two H. heptaphyllus populations, using microsatellite markers, to estimate the number of seed trees for seed collection procedures. To do that, open pollinated seeds were collected from 15 seed trees in a Lageado population and from 15 at Véu da Noiva. Population multilocus outcrossing rate ( ) was equal for the two provenances ( = 1.0), however we observed individual variation for outcrossing rate among trees (0.68 to 0.99). The rate of mating among relatives ( , minimum of 0.21) and multilocus paternity correlation ( , minimum of 0.11) were substantial in both populations, where 97% of the trees crossed with relatives. This suggests a spatial genetic structure in the populations from where seeds were harvested. Due to correlated mating, the co-ancestry within progenies was higher ( minimum of 0.139) and effective size was smaller ( maximum of 3.07) than the expected in half-sibs ( = 0.125, = 4). Consequently, the number of seed trees for seed harvest for breeding, conservation, and reforestation programs must be at least 49.
Mating system in Handroanthus heptaphyllus (Vell.) Mattos populations and its implications for seed collection to genetic conservation and breeding
Keywords: Genetic diversity; Mating systems; Microsatellite molecular markers; Progenies